Pola Anak Atas Penitipan Orang Tua di Panti Jompo UPTD Pelayanan Sosial Lanjut Usia Kisaran-Rantau Prapat Dalam Perspektif Hukum Islam - Prishela, Cindy Salwa; Milhan, Milhan (UIN Fatmawati Sukarno Bengkulu, 2026)
Abstract: This study aims to analyze the factors that lead children to place elderly parents in nursing homes and to assess the legal status of this practice from the perspective of Islamic law using a maqāṣid al-sharīʿah approach. The study employs a qualitative non-doctrinal method with a descriptive design, collecting primary data through interviews with elderly residents of the institution, the families who placed them there, and the administrators of the UPTD Social Services for the Elderly Kisaran–Rantau Prapat, supported by observation and document study. The findings indicate that parental placement is influenced by economic factors, the children’s busyness, the physical and mental health conditions of the elderly, weak family communication, and the elders’ desire for a peaceful life. From the perspective of Islamic law, the practice of placing parents in nursing homes may be categorized as haram, makruh, or mubah depending on the existence of a sharʿī excuse (udzur), the fulfillment of the parents’ rights, and the preservation of the emotional bond between children and parents. If such placement is consistent with the principles of maqāṣid al-sharīʿah-particularly in safeguarding religion, life, intellect, lineage, and property-then it can be justified in sharʿī terms as an effort to realize the maslahah (welfare) of the elderly.Keywords: nursing home; birr al-walidain (filial piety); maqāṣid al-sharīʿah; elderly; parental placement. Abstrak: Penelitian ini bertujuan menganalisis faktor-faktor penyebab anak menitipkan orang tua lanjut usia ke panti jompo serta menilai status hukumnya dalam perspektif hukum Islam melalui pendekatan maqāṣid al-syarīʻah. Penelitian ini menggunakan metode kualitatif non-doktrinal dengan pendekatan deskriptif, dengan pengumpulan data primer melalui wawancara terhadap lansia penghuni panti, keluarga yang menitipkan, serta pengelola UPTD Pelayanan Sosial Lanjut Usia Kisaran–Rantau Prapat, yang didukung oleh observasi dan studi dokumentasi. Hasil penelitian menunjukkan bahwa penitipan orang tua dipengaruhi oleh faktor ekonomi, kesibukan anak, kondisi kesehatan fisik dan mental lansia, lemahnya komunikasi keluarga, serta keinginan lansia untuk memperoleh ketenangan hidup. Dalam perspektif hukum Islam, praktik penitipan orang tua ke panti jompo dapat berkategori haram, makruh, atau mubah tergantung pada adanya udzur syar’i, pemenuhan hak-hak orang tua, serta tetap terjaganya hubungan emosional antara anak dan orang tua. Apabila praktik penitipan tersebut sejalan dengan prinsip maqāṣid al-syarīʻah, terutama dalam menjaga agama, jiwa, akal, keturunan, dan harta, maka penitipan dapat dibenarkan secara syar’i sebagai upaya mewujudkan kemaslahatan bagi lansia.Kata Kunci: Panti jompo; Birrul walidain; Maqashid syari’ah; Lansia; Penitipan orang tua.